2022
DOI: 10.3390/ijerph19031058
|View full text |Cite
|
Sign up to set email alerts
|

Five Different Lives after Suffering from Spinal Cord Injury: The Experiences of Nurses Who Take Care of Spinal Cord Injury Patients

Abstract: According to statistics of Ministry of Health and Welfare, accidents were the sixth common causes of death in Taiwan in 2016. A total of 1200 new cases of spinal cord injury each year are caused by accidents and adverse effects. This study explored nurses’ experience of caring for patients with spinal cord injury. Hermeneutic phenomenology was used in the data analysis. The five themes emerged: dramatic changes in life, life lost control, life after catastrophic injury, life takes turns for the worse for famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This result disagrees with El-Aqoul et al (19) in their study reported that more than half of the studied nurses were male. While, this finding is congruent with Wang et al (6) in their study reported that majority of nurses were married.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result disagrees with El-Aqoul et al (19) in their study reported that more than half of the studied nurses were male. While, this finding is congruent with Wang et al (6) in their study reported that majority of nurses were married.…”
Section: Discussionsupporting
confidence: 90%
“…The greatest outcomes for patients should be promoted by nurses working as a multidisciplinary team to deliver effective nursing care that can stop or lessen future SCI. In addition to providing medical care, promoting patients' psychological well-being, implementing nursing plans based on scientific nursing theory and evidence-based practice, delivering education, and evaluating appropriate medical services for patients and their caregivers, nurses also play an important role in patient education (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Past interpretive phenomenologists have successfully used the seven steps of Colaizzi to analyse data (e.g. Domaradzki, 2022; Wang et al, 2022). The following steps were followed: 1. interviews were transcribed, read, and reread; 2. significant statements were identified; 3. meaning of statements were considered; 4. significant statements were organized under themes according to an understood meaning; 5. an exhaustive description of the phenomenon was created; 6. the fundamental structure and meaning of the phenomenon as shared by the participants was formed into a statement; and 7. the fundamental structure statement was validated (Colaizzi, 1978).…”
Section: Methodsmentioning
confidence: 99%
“…Past interpretive phenomenologists have successfully used the seven steps of Colaizzi to analyse data (e.g. Domaradzki, 2022;Wang et al, 2022).…”
Section: Ethical Considerationsmentioning
confidence: 99%